Efektivitas Bimbingan Kelompok Teknik Homeroom Untuk Mengurangi Kecemasan Remaja Perempuan Dalam Menghadapi Menarche - Zuhdi, Muhammad Sholihuddin; As-Shodiq, Mohammad Ja'far (Universitas Nusantara PGRI Kediri, 2023)
A girl is said to be in puberty when she experiences menstruation or commonly referred to as menarche, this happens a lot to children in Pikatan Village, this requires help to gain knowledge so that the child does not experience anxiety about experiencing Menarche, using the Homeroom Technique, as for the purpose The purpose of this study was to determine the effectiveness of the Homeroome technique to reduce anxiety in children who are experiencing menarche by using the experimental type of quantitative research method, for the results of hypothesis testing to obtain the results that the results of the pired sample t-test in the table, it can be seen the output results (paired). The first sample t-test obtained a Sig (2-tailed) value of 0.000 <0.05. So, there is a difference in the average results of the homeroom technique group guidance for the experimental class pre-test with the experimental class post-test with menarche anxiety guidance material.